Distribution and Habitat Use of a Cryptic Small Cetacean, the Burmeister's Porpoise, Monitored From a Small-Scale Fishery Platform - Clay, Thomas A.; Mangel, Jeffrey C.; Alfaro-Shigueto, Joanna; Hodgson, David J.; Godley, Brendan J. (Frontiers in Marine Science, 2018)
There is widespread evidence that small-scale fisheries (SSF) bycatch threatens many populations of small cetaceans, yet conservation efforts are often limited by a lack of basic knowledge regarding their abundance, distribution, and habitat use. Here, we used passive acoustic monitoring from an SSF platform-of-opportunity to better characterize the distribution and habitat use of small cetaceans in northern Peru, focussing on the little-known Burmeister's porpoise Phocoena spinipinnis. From 2009 to 2012, acoustic click detectors (C-PODs) were attached to fishing nets for the duration of 116 fishing sets (30 fishing trips). Dolphins (unspecified delphinids) and porpoises were recorded around 71 and 22% of fishing sets, respectively. The probability of occurrence and buzzing behavior (a proxy for foraging), and time spent, were linked to both static and dynamic environmental variables to examine the drivers of habitat use. Dolphin activity was spread evenly throughout the fishing area and was not linked to any habitat variables. In contrast, porpoises were detected in neritic waters, and habitat models performed well, identifying preferences for shallow (<200 m depth) and cooler (17–18°C) waters, close (<50 km) to shore. The high bycatch rate of small cetaceans in Peruvian SSF gave us the unique opportunity to investigate the link between bycatch and cetacean activity around vessels. We found a positive relationship between the likelihood of a bycatch event and acoustic presence for both dolphins and porpoises, however as we did not know the timing of entanglement, we could not link vocalization rates to mortality events. Nonetheless, as small cetaceans (particularly dolphins) frequently encounter fishing boats, the likelihood of entanglements may be reduced through effective efforts to alert animals to the presence of the net, either acoustically (using acoustic alarms) or visually. This study demonstrates that passive acoustic monitoring from a fisheries platform can provide insights into the distribution and habitat use of small cetaceans at relatively low cost, and is likely to be suitable in regions with low monitoring effort and high fishing pressure.